PENGARUH VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR IPAS MATERI INDONESIAKU KAYA BUDAYA SISWA KELAS IV SD NEGERI 230 PALEMBANG - Sri Hartati; Rury Rizhardi; Ida Suryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether there is an effect of using video learning media on the results of learning science on the material of Indonesiaku Kaya Budaya of grade IV students of SD Negeri 230 Palembang. The approach used is quantitative experiment. The research design uses Quasi Experimental Design with the Nonequivalent Control Group Design model. Data collection techniques in this study are observation, tests (pretest and posttest), and documentation. The results of data processing show the average value of the posttest test in the experimental class is 77.19, while in the control class it is 66.21. Based on the normality test, it was obtained that the sample came from a normally distributed population. The homogeneity test shows that the sample came from a homogeneous population. The results of the t-test calculation using the independent sample t-test significant 2-tailed ≤ 0.025 then Ho is rejected, if significant (2-tailed) ˃ 0.025 Ha is accepted. Based on the results of the analysis and discussion of the data, it can be concluded that the use of video learning media has a significant effect on improving the results of learning science on the material of Indonesiaku Kaya Budaya of grade IV students of SD Negeri 230 Palembang.